TOGA Education and Socialization: Building Nature-Based Family Health - siti mardhika sari; Dewi, Tyas Soemarah Kurnia; Suprapti, Endang; Aziez, Achmad Fatchul; Haryuni; Daryanti (Journal of Community Capacity Empowerment, 2025)
The community’s demand for medicinal plants continues to grow along with the back to nature trend, which encourages the use of natural ingredients to maintain health. However, in Karangmojo Village, Weru Subdistrict, Sukoharjo Regency, many home gardens remain underutilized, even though they have the potential to serve as a source of Family Medicinal Plants (TOGA). This community service program aimed to improve the knowledge and skills of members of the Family Welfare Empowerment (PKK) group in cultivating TOGA to support family health self-reliance. The program was conducted on January 15, 2025, at the Karangmojo Village Hall using a participatory approach, including counseling, technical training, field practice, and mentoring. Participants were introduced to various medicinal plants that are easy to cultivate, planting and maintenance techniques, as well as their applications for simple home remedies. The results showed a significant increase in participants’ knowledge and skills, reflected in their high enthusiasm during practice and their commitment to developing TOGA gardens in their respective yards. A demonstration TOGA garden was successfully established in one participant’s yard as a replicable model. This activity not only provided direct benefits for family health but also opened up economic opportunities through processing harvested medicinal plants into marketable herbal products. The program is expected to be sustainable with continuous mentoring and the establishment of a village-level TOGA working group.